Secretory IgA Deficiency in Individual Small Airways Is Associated with Persistent Inflammation and Remodeling - Polosukhin, Vasiliy V. (Am J Respir Crit Care Med, 2017)
Rationale: Maintenance of a surface immune barrier is important for homeostasis in organs with mucosal surfaces that interface with the external environment; however, the role of the mucosal immune system in chronic lung diseases is incompletely understood. Objectives: We examined the relationship between secretory IgA (SIgA) on the mucosal surface of small airways and parameters of inflammation and airway wall remodeling in chronic obstructive pulmonary disease (COPD). Methods: We studied 1,104 small airways (<2 mm in diameter) from 50 former smokers with COPD and 39 control subjects. Small airways were identified on serial tissue sections and examined for epithelial morphology, SIgA, bacterial DNA, nuclear factor-κB activation, neutrophil and macrophage infiltration, and airway wall thickness. Measurements and Main Results: Morphometric evaluation of small airways revealed increased mean airway wall thickness and inflammatory cell counts in lungs from patients with COPD compared with control subjects, whereas SIgA level on the mucosal surface was decreased. However, when small airways were classified as SIgA intact or SIgA deficient, we found that pathologic changes were localized almost exclusively to SIgA-deficient airways, regardless of study group. SIgA-deficient airways were characterized by (1) abnormal epithelial morphology, (2) invasion of bacteria across the apical epithelial barrier, (3) nuclear factor-κB activation, (4) accumulation of macrophages and neutrophils, and (5) fibrotic remodeling of the airway wall. Conclusions: Our findings support the concept that localized, acquired SIgA deficiency in individual small airways of patients with COPD allows colonizing bacteria to cross the epithelial barrier and drive persistent inflammation and airway wall remodeling, even after smoking cessation.